Fluoride Exposure Suppresses Proliferation and Enhances Endoplasmic Reticulum Stress and Apoptosis Pathways in Hepatocytes by Downregulating Sirtuin-1. (21st August 2022) - Yu, Yanlong; Li, Ling; Yu, Wenfeng; Guan, Zhizhong
Abstract : Objective . To explore the function and mechanism of Sirt-1 in fluorine-induced liver injury. Method . Fluorosis rats were first established. The fluorine content, pathological structure, collagen fibers, and fibrosis in liver tissues were tested through the fluoride ion selective electrode method, H&E, Masson, and Sirius red staining; alanine aminotransferase (ALT), aspartate aminotransferase (AST), interleukin 18 (IL-18), and tumor necrosis factor- α (TNF- α ) levels in rat serum were also analyzed using ELISA kits. Then, the fluorosis cell model was built, which was also alleviated with NaF, Sirt-1 siRNAs, or endoplasmic reticulum stress (ERS) alleviator (4-PBA). CCK-8 also assessed cell proliferation; RT-qPCR or Western blots detect sirtuin-1 (Sirt-1), protein kinase R- (PKR-) like endoplasmic reticulum kinase (PERK), and endoplasmic reticulum stress (ERS) and apoptosis-related protein levels in liver tissue. Results . Our results uncovered that fluorine exposure could aggravate the pathological damage and fibrosis of rat liver tissues and increase indicators related to liver injury. And fluoride exposure also could downregulate Sirt-1 and upregulate ERS-related proteins (PERK, 78-kD glucose-regulated protein (GRP-78), and activating transcription factor 6 (ATF6)) and apoptosis-related protein (caspase-3 and C/EBP-homologous protein (CHOP)) in rat liver tissues. Besides, we proved that fluoride exposure could suppress proliferation and enhances ERS and apoptotic pathways in AML12 cells by downregulating Sirt-1. Moreover, we revealed that ERS alleviator (4-PBA) could induce proliferation and prevent ERS and apoptosis in fluorine-exposed AML12 cells. Conclusions . We suggested that fluorine exposure can induce hepatocyte ERS and apoptosis through downregulation of Sirt-1.